(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article analyzes the physical, chemical and structural properties of fire-resistant building materials and evaluates their role in ensuring the fire safety of modern buildings. It discusses traditional materials such as brick and concrete, as well as advanced materials such as basalt fiber composites, mineral wool, gypsum board and intumescent coatings. International fire safety standards (ISO, EN, UL, NFPA) and their implementation in Uzbekistan are also examined. The article concludes with an overview of emerging technologies, including nanomaterials and smart fire-protective systems.